Boron dopant simultaneously achieving nanostructure control and electronic structure tuning of graphitic carbon nitride with enhanced photocatalytic activity. Issue 41 (12th October 2021) - Wang, Xin; Liu, Boyan; Xiao, Xiong; Wang, Songcan; Huang, Wei
Abstract : The boron-doped graphitic carbon nitride synthesized by two-step heat treatment has a one-dimensional tubular structure and its hydrogen evolution is 2 times higher than that of undoped g-C3 N4 . Abstract : Graphitic carbon nitride (g-C3 N4 ) has been widely studied for photocatalysis due to its suitable band structure, tunable bandgap and low cost. Nevertheless, the photocatalytic performance of bulk g-C3 N4 is poor because of the severe charge recombination. Herein, a facile two-step thermal treatment approach is proposed to prepare boron doped g-C3 N4 with adjoined nanotubular structures by adding a small amount of H3 BO3 in urea. Interestingly, nanostructure evolution of the g-C3 N4 from nanosheets to adjoined nanotubes can be obtained by tuning the amount of H3 BO3 . The obtained g-C3 N4 adjoined nanotubes with optimal boron doping exhibit an excellent photocatalytic hydrogen production rate of 3.8 mmol g −1 h −1, which is approximately 2 times higher than its pristine g-C3 N4 counterpart. Furthermore, a high apparent quantum efficiency of 14.46% is achieved at 420 nm. Systematical studies reveal that the enhanced photocatalytic hydrogen evolution performance stems from the synergistic effect of boron doping and adjoined nanotube structures that promotes charge transport and separation. The new finding provides a simple strategy to achieve simultaneous doping and nanostructured control for the design of efficient photocatalysts.